Women and Sufism: Perspectives on History, Gender, and the Contemporary Application of Maqāṣid al-Sharīʿah - Tandos, Rosita; Kuba, Amiruddin (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2026)
This article examines the role of women in Sufism from the perspective of Islamic law, focusing on their spiritual practices, historical contributions, and contemporary relevance. It employs a qualitative interpretive approach, drawing on literature analysis, observations of online Sufi learning activities, and semi-structured interviews with women participating in Sufi study circles. The analysis is grounded in Jasser Auda’s Maqāṣid al-Sharīʿah framework, through which women’s spiritual engagement is assessed in relation to key legal objectives, including the preservation of religion (ḥifẓ al-dīn), life (ḥifẓ al-nafs), intellect (ḥifẓ al-‘aql), lineage (ḥifẓ al-nasl), and human dignity (ḥifẓ al-karāmah al-insāniyyah). The findings demonstrate that Sufi teachings, which emphasize spiritual equality and inner transformation, provide a normative Islamic basis for women’s active participation as spiritual leaders, intellectuals, and social actors. The study contributes to Islamic legal discourse by showing that women’s engagement in Sufism represents a viable and internally grounded framework for advancing gender equity and holistic human well-being within the tradition.